Connectivity: insights from the U.S. Long Term Ecological Research Network. Issue 5 (17th May 2021) - Iwaniec, David M.; Gooseff, Michael; Suding, Katharine N.; Samuel Johnson, David; Reed, Daniel C.; Peters, Debra P. C.; Adams, Byron; Barrett, John E.; Bestelmeyer, Brandon T.; Castorani, Max C. N.; Cook, Elizabeth M.; Davidson, Melissa J.; et al.
Abstract: Ecosystems across the United States are changing in complex and surprising ways. Ongoing demand for critical ecosystem services requires an understanding of the populations and communities in these ecosystems in the future. This paper represents a synthesis effort of the U.S. National Science Foundation‐funded Long‐Term Ecological Research (LTER) network addressing the core research area of "populations and communities." The objective of this effort was to show the importance of long‐term data collection and experiments for addressing the hardest questions in scientific ecology that have significant implications for environmental policy and management. Each LTER site developed at least one compelling case study about what their site could look like in 50–100 yr as human and environmental drivers influencing specific ecosystems change. As the case studies were prepared, five themes emerged, and the studies were grouped into papers in this LTER Futures Special Feature addressing state change, connectivity, resilience, time lags, and cascading effects. This paper addresses the "connectivity" theme and has examples from the Phoenix (urban), Niwot Ridge (alpine tundra), McMurdo Dry Valleys (polar desert), Plum Island (coastal), Santa Barbara Coastal (coastal), and Jornada (arid grassland and shrubland) sites. Connectivity has multiple dimensions, ranging from multi‐scalar interactions in space to complex interactions over time that govern the transport of materials and the distribution and movement of organisms. The case studies presented here range widely, showing how land‐use legacies interact with climate to alter the structure and function of arid ecosystems and flows of resources and organisms in Antarctic polar desert, alpine, urban, and coastal marine ecosystems. Long‐term ecological research demonstrates that connectivity can, in some circumstances, sustain valuable ecosystem functions, such as the persistence of foundation species and their associated biodiversity or, it can be an agent of state change, as when it increases wind and water erosion. Increased connectivity due to warming can also lead to species range expansions or contractions and the introduction of undesirable species. Continued long‐term studies are essential for addressing the complexities of connectivity. The diversity of ecosystems within the LTER network is a strong platform for these studies.